ELABORATION OF A DIGITAL MARKETING PLAN FOR MICROENTERPRISE SERVICE PROVIDERS IN THE AREA OF INFORMATION TECHNOLOGY - Irano Valentim, Daniel; Carleto, Nivaldo (Revista Interface Tecnológica, 2020)
The objective of this work was to present a methodology for the elaboration of a digital marketing plan suitable for a micro company providing services in the area of information technology. For its development, some research techniques were used, such as: bibliographic, exploratory, quantitative and qualitative researches. The results obtained showed that for a micro company to conquer its space in the corporate scenario, dominated by medium and large companies, it becomes necessary to carry out a digital marketing plan, thus, establishing an executive planning through a SWOT (Strengths - strong points; Weaknesses - weak points; Opportunities - opportunities for its business; Threats - threats to its business) and, above all, identifying its target audience. Therefore, it was possible to conclude that the proposed methodology was consistent with the existing market conditions in the current corporate scenario, considering, above all, a demanding and differentiated target audience. In addition, it is important to emphasize that the tools of digital marketing are essential for monitoring the demands and needs of consumers, who have been seeking for new forms of service in the area of information technology.